135 A tale of two settings: are there differences in hospice inpatient initial needs & outcomes depending on where the patient is admitted from?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Malik, FA; Clarke, S; Barclay, D
Abstract : Introduction: Understanding patient needs and assessing outcomes are important to improve quality of care. As part of an ongoing evaluation of hospice inpatient (IPU) bed use, the needs & outcomes of those admitted to the IPU from the local hospital trust and from community settings were compared to examine if there were differences depending on settings admitted from. Methods: Cross-sectional retrospective analysis of consecutive IPU admissions from the local hospital NHS Trust (HA) and admissions from the community (CA) to a specialist palliative 14-bedded hospice from August 16–March 17. Data items collected include patient demographics & outcome data e.g. IPU admission IPOS, phase of illness (PoI) & AKPS. All data anonymised. Results analyzed and descriptive statistics utilized. Results: 50 HA and 113 CA admissions during the time period (in addition 24 respite admissions and 6 'out of area' HA not used in analysis). There were no differences in mean age (HA 71.3 yrs, CA 71 yrs) or gender (HA 60%, CA 53% male) and no difference in malignant diagnosis between groups (HA 82%, CA 88%). IPU admission mean AKPS was worse in HA (33) than CA (44.6) (p<0.005) but no difference in mean IPOS (HA 31.2, CA 34, p=0.1). HA patients were more likely to be in the 'dying phase' (PoI) on IPU admission (14/50, 28%) compared to other phases than CA patients (9/110, 8%) (p<0.001). Mean IPU length of stay was longer in CA (17.6 days) compared to HA (13.2 days) (p=0.05). HA were more likely to die during that IPU admission compared to CA patients (46/50 (92%) vs 69/110 (62%)), (p<0.05). 41/110 CA patients were discharged from IPU. Conclusions: Findings highlight potential differences in patient needs and outcomes depending on which setting the patient was admitted from. This will influence development of 24/7 services & bed utilization. Further analysis is beneficial to clarify findings.